2016
DOI: 10.4049/jimmunol.1500481
|View full text |Cite
|
Sign up to set email alerts
|

MiR-381-3p Regulates the Antigen-Presenting Capability of Dendritic Cells and Represses Antituberculosis Cellular Immune Responses by Targeting CD1c

Abstract: Tuberculosis is still the widest spread infectious disease in the world, and more in-depth studies are needed on the interaction between the pathogen and the host. Due to the highest lipid components in Mycobacterium tuberculosis, the CD1 family that specifically presents antigenic lipids plays important roles in the antituberculosis immunity, especially CD1c, which functions as the intracellular Ag inspector at the full intracellular range. However, downregulation of the CD1c mRNA level has been observed in M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…Target genes of miR-381-3p are known to be involved in cellular processes and cellular macromolecule metabolism 23 . Notably, miR-381-3p mediates antigen-presenting ability in dendritic cells and anti-tuberculosis cellular immune responses by targeting CD1c 24 . In this study, we revealed that miR-381-3p directly targeted 3′ UTR of ETS2 and reduced the expression of ETS2.…”
Section: Discussionmentioning
confidence: 71%
“…Target genes of miR-381-3p are known to be involved in cellular processes and cellular macromolecule metabolism 23 . Notably, miR-381-3p mediates antigen-presenting ability in dendritic cells and anti-tuberculosis cellular immune responses by targeting CD1c 24 . In this study, we revealed that miR-381-3p directly targeted 3′ UTR of ETS2 and reduced the expression of ETS2.…”
Section: Discussionmentioning
confidence: 71%
“…Previous studies have shown that miR-381-3p may be a target for the treatment of patients with TB or HIV-associated neurocognitive disorders 41 , 42 . To determine the clinical significance of miR-381-3p in patients with intestinal I/R injury, we measured the expression of miR-381-3p and associated proteins in ischemic intestinal tissues and normal tissues from clinical patients.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, miR-301 was also up-regulated in T cells in the central nervous system of animals with experimental autoimmune encephalomyelitis ( Mycko et al, 2012 ), an animal model for the process of autoimmune demyelination occurring during multiple sclerosis, a disease with a possible association with HHV-6 infection ( Leibovitch and Jacobson, 2014 ). The up-regulated miR-101 and miR-381 are involved in the polarization and activation of the cells of the innate immune compartment, regulating the inflammatory response ( Zhu et al, 2010 ; Essandoh et al, 2016 ; Wen et al, 2016 ); the increased miR-548 may represent a mechanism facilitating viral pathogenesis as it negatively correlates with IFNγR1 levels ( Xing et al, 2014 ). miR-21 and miR-590, up-regulated by HHV-6A, are involved in differentiation and activation of T cells, particularly during autoimmunity ( Sousa et al, 2017 ), with miR-590 also down-regulating critical genes of signaling pathways similar in cancer and inflammation ( Sheikholeslami et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%